DNA sequence of the viral and cellular src gene of chickens. 1. Complete nucleotide sequence of an EcoRI fragment of recovered avian sarcoma virus which codes for gp37 and pp60src. - Takeya, T (1982)
Recovered avian sarcoma virus is a class of virus obtained from chicken tumors induced by mutants of Rous sarcoma virus which have a deletion in the src gene. We have determined the entire nucleotide sequence of a 3.1-kilobase EcoRI DNA fragment of molecularly cloned recovered avian sarcoma virus DNA. This DNA fragment contains part of the env gene and the entire src gene. Amino acid sequences of both gene products were deduced from the DNA sequences; the predicted amino acid sequences were verified by protein studies. An env protein (gp37) was found to be composed of 205 amino acids with three glycosylation sites. gp37 had a long stretch of hydrophobic residues near the carboxyl terminus. The src gene product, pp60src, was composed of 526 amino acids and contained the possible sites for tyrosine and serine phosphorylation. The amino acid sequences predicted in this study differ significantly from the amino acid sequence predicted previously for the Schmidt-Ruppin strain of Rous sarcoma virus.